Peran Regulasi Nasional dan Perjanjian Bilateral Dalam Penyelesaian Sengketa Menurut Hukum Bisnis di Indonesia - Dwi Sukma Ramdhani; Gunardi, Gunardi (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
The development of international business must be based on clear legal certainty for investors and business actors in Indonesia. National regulations form the main legal basis, while bilateral agreements provide additional protection for foreign investors. This study aims to analyze the interaction between the national legal framework and international commitments, particularly in the context of bilateral investment agreements. The approach used is normative juridical with literature study and document analysis. The results of the study show that national regulations provide domestic legal certainty, while bilateral agreements strengthen international cooperation and facilitate foreign investment. However, potential conflicts may arise when national regulations are not fully aligned with international agreements, requiring careful legal harmonization. In conclusion, Indonesia needs to strengthen its regulatory framework to be compatible with bilateral agreements in order to create a conducive and competitive business climate..